2012
DOI: 10.1258/la.2012.011115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating methods of mouse euthanasia on the oocyte quality: cervical dislocation versus isoflurane inhalation

Abstract: Cervical dislocation is a commonly used method of mouse euthanasia. Euthanasia by isoflurane inhalation is an alternative method which allows the sacrifice of several mice at the same time with an anaesthesia, in the aim to decrease pain and animal distress. The objective of our study was to assess the impact of these two methods of euthanasia on the quality of mouse oocytes. By administering gonadotropins, we induced a superovulation in CD1 female mice. Mice were randomly assigned to euthanasia with cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
(10 reference statements)
0
28
0
1
Order By: Relevance
“…Three days later, they received an additional injection with 0.1 mL of 5 IU of Human Chorionic Gonadotropin. Sixteen hours later, mice were sacrificed by cervical dislocation [58] and oviducts were collected. Intact cumulus masses were released from excised oviducts, and decoronisation was performed after incubation with hyaluronidase (10 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Three days later, they received an additional injection with 0.1 mL of 5 IU of Human Chorionic Gonadotropin. Sixteen hours later, mice were sacrificed by cervical dislocation [58] and oviducts were collected. Intact cumulus masses were released from excised oviducts, and decoronisation was performed after incubation with hyaluronidase (10 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…These significantly higher incidence of PCGE in oocytes derived from L CO 2 euthanasia group may explain the lower two‐cell development after IVF. A previous study found that euthanasia via isoflurane inhalation resulted in significantly higher morphologically abnormal MII mouse oocytes (Roustan et al, ) which might cause by some other mechanism such as hypothermia or isoflurane toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Mice are the most commonly used laboratory animals for biomedical research and production of genetically engineered animal models for human disease and disorders (Berthelot‐Ricou et al, ; Kulandavelu et al, ; Roustan et al, ). The main principles of animal use in biomedical research are defined as 3Rs namely, replacement, reduction, and refinement.…”
Section: Introductionmentioning
confidence: 99%
“…Automated carbon dioxide euthanasia systems have been validated and are commercially available (McIntyre et al, 2007). Cervical dislocation and decapitation of mice and rats less than 200 g can be rapid and humane if carried out by experienced operators, who were preferably trained on anesthetized animals, and as approved by the IACUC (Carbone et al, 2012b;Cartner et al, 2007;Golledge, 2012;Roustan et al, 2012;Leary et al, 2013). Guinea pigs may struggle excessively when exposed to carbon dioxide.…”
Section: H Euthanasiamentioning
confidence: 99%